Organizações policiais no estado de São Paulo: dificuldades de integração e mecanismos de controle - Alves, Fernando Antonio da Silva (2004)
The objectives of this master of sciences dissertation was leading studies about the first police organizations historically acting in São Paulo: the civil police and rnilitary police. Watching the police experiences in some places of São Paulo, mainly in São Paulo city, the studies looked for observing the intense rivalry historically existed among the police organizations, colleting the reasons of rivalry to justify the integration difficulties between organizations in formation of a completed cycle of polire services based on duality prevention-repression. Initially, the problem is presented through the narration of real cases registered in peaces of police reports and criminal occurrence inscriptions, which situations envelops military and civil policemen in conflict relation. It follows a brief historical summary of the police organizations acting in the country, for necessity to conceptualize the origin fiom the first models of policing likes military police and civil polire. lt follows the next period that shows the influence of this models in formation the polire organizations in the country, mainly in São Paulo state. The theme about the São Paulo's police organizations proceeds with the historical definition of police acting during the after-64 period to referee distinct police cultures existed in police, also the power mechanisms will arder this police organizations acting. It presents forms of individual unless satisfactions in the police officers that serve like a motive to initiate the rights movements, observing rare moments ofsincere police integration. After, the reforming police proposals are approved, in a reality of contention of policing crisis face on the absence of integration. Also, the political proposals of socialist parties in the 2002 election to the republic presidency and the governar of state, about the public security and police reforming, were observed in this studies, in perspective to solve the policing conflicts. The municipal guards were observed in the quality of contrai mechanisms and agents of police practices in the cities of São Paulo state, and their inclusion of discussion about rivalry police, as well it's observed the proposals about the utilization of federal police effectives to improving the police servires in São Paulo. At last, the dissertation analyses the maintenance of the actual police models during a disciplinary society, fixing on the social foundation of the existence and rivalry among the existed police organizations